2014
DOI: 10.1097/rlu.0000000000000451
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Thrombus

Abstract: This study supports results from other smaller studies regarding the usefulness of FDG PET/CT in TT and corroborates the hypothesis that the SUVmax and the patterns of FDG uptake can be helpful for differentiating BT from TT in oncological patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The difference in SUV max was significant. In Ravina’s series (31), out of 21 tumor thrombosis cases incidentally detected by FDG PET/CT, 6 were from RCCs. Ferda et al also reported that FDG PET/CT successfully detected all 7 cases with tumor invasion into the inferior vena cava of 60 patients with RCC (19).…”
Section: Fdg Pet/ct For Restaging Rccmentioning
confidence: 99%
“…The difference in SUV max was significant. In Ravina’s series (31), out of 21 tumor thrombosis cases incidentally detected by FDG PET/CT, 6 were from RCCs. Ferda et al also reported that FDG PET/CT successfully detected all 7 cases with tumor invasion into the inferior vena cava of 60 patients with RCC (19).…”
Section: Fdg Pet/ct For Restaging Rccmentioning
confidence: 99%
“…Bland non-catheter-related thrombus often has a lower SUV max compared to tumor thrombus. In general, SUV max greater than 3.35–3.63, contiguous intravascular spread from larger tumor, and location in the IVC have all been associated with tumor rather than bland thrombus [57]. …”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that an inflammatory process surrounding chronic bland thrombus is responsible for associated FDG avidity [1, 2, 5]. When FDG activity occurs at the tip of the catheter that was used for the injection, physical FDG trapping becomes another possibility [1].…”
Section: Discussionmentioning
confidence: 99%
“…Higher risk, larger tumors are more FDG PET avid. For local staging FDG PET has been found useful in determining whether thrombus in the renal vein and inferior vena cava is malignant or “bland” 6 , a distinction that is considered important by some surgeons 7 . In general CT, MRI and bone scan in symptomatic patients are considered sufficient staging studies to clear a patient for surgery.…”
Section: Use Of Pet In Renal Cell Carcinomamentioning
confidence: 99%